Estudo do espectro eletrônico da molécula ditienil-dicetopirrolopirrol com o uso da teoria do funcional da densidade dependente do tempo - Araujo, Luis Octavio de (2020)
Using the time-dependent density functional theory, the S0→S1 electronic spectrum of the 2,5-dihexyl-3,6-di(thiophen-2-yl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione molecule (DPP2T) was investigated, analyzing the performance of adiabatic and vertical models for its computational simulation. Three exchange-correlation functionals were compared (B3LYP, CAMB3LYP and M06), and the solvent (CHCl3) effects were simulated using the polarizable continuum model (PCM). The calculated spectra proved to be in good agreement with the experimental one, correlating in about 97-99% with the latter. At the low temperature limit, it was found that the main vibronic transitions that give the investigated spectrum its characteristic shape are the zero-phonon transition and fundamental transitions. According to the Adiabatic Hessian (AH) model, the most intense fundamental transition is related to the stretch normal mode, symmetrical and in plane, of the carbon-carbon bonds of the DPP2T π-conjugated skeleton, which is quinoidized upon S0→S1 electronic transition. The adiabatic shift (AS) and linear coupling (LCM) models, implemented in the TDSPEC code, showed that the formats of the absorption spectra predicted by them do not undergo major changes in relation to the AH spectrum. Disregarding the distortion of harmonic frequencies, for example, only shifts the AS spectrum by about 0.07 eV towards blue with respect to AH one. Regarding the charge transfer that would be associated with the S0→S1 transition investigated, it was found that, contrary to what the literature states, the calculation of the electronic density rearrangement suggests that such a transition does not culminate in this type of transfer, which would supposedly occur from thiophene rings to diketopyrrolopyrrole ring. This shows how detailed investigations about the spectrum and electronic structure of a molecule can reveal a wealth of information about it, making it possible to interpret the experimental data in a more concrete and grounded way than that which would be done on purely phenomenological bases.